Meningococcal infection and proteolytic control. Issue 12 (December 1978) - Stark, J M; Matthews, N; Ryley, H C; Greenwood, B M; Lewis, L S; Whittle, H C
Abstract : Cascade enzyme inhibitors (C1-esterase inhibitor, C3b inactivator, antithrombin III) and other major proteolytic enzyme inhibitors (alpha 1 trypsin inhibitor, alpha 1 chymotrypsin inhibitor, inter-alpha-trypsin inhibitor, alpha 2 macroglobulin) as well as C3 and alpha 1 acid glycoprotein, have been examined in the sera of Nigerian patients suffering from meningococcal infection of varied severity. Patients with meningococcaemia had lower serum concentrations of important inhibitors than did patients with localised meningitic infection. Within the coccaemic group, those who died had the lowest values, notably of antithrombin III and alpha 2 macroglobulin (and also of C3). The clinical end-result of meningococcal infection may be related to the degree of disequilibrium of the linked system of proteolytic control induced by the meningococcal endotoxin.